Positioning Strategy Design of Online Travel Agent Applications Based on Perceptual Mapping - Muhammad Fadhil Rafif; Sari Wulandari; Boby Hera Sagita (School of Industrial and System Engineering, Telkom University, 2022)
Kliktrip is one of the online travel agent application brands with day trip and activity booking servicesin Indonesia which was established in 2018. In the last few years, Kliktrip has experienced severalsymptoms, including a decrease in revenue in the second year and the low level of branddifferentiation of the Kliktrip online travel agent application based on customer perception comparedto other online travel agent application brands. Based on the symptoms of these problems, it can beconcluded that the brand of the Kliktrip online travel agent application is weak in customerperceptions of the online travel agent application because customers tend not to know the advantagesoffered by the Kliktrip online travel agent application brand. To be successful in facing competitionwith other business competitors, it is necessary to carry out sustainable development by buildingcompetitive differentiation by designing and improving positioning strategies. Based on the results ofthe perceptual mapping, there were 4 groups of competitive areas, the online travel agent Kliktripapplication brand was in the same area as the Explorer.id online travel agent application brand whichmade it the main competitor of the Kliktrip online travel agent application brand. The objectives ofthis research are to (1) Design a strategy for improving the brand positioning of the online travel agentapplication and (2) Optimize the resources owned by the Kliktrip online travel agent application brandto implement a strategy for improving the brand positioning of the Kliktrip online travel agentapplication.